Nanoparticles suppress fluid instabilities in the thermal drawing of ultralong nanowires - Injoo Hwang (Nature Portfolio, 2020)
Thermal drawing of glass-cladded metal nanowires is limited by fluid instabilities. Hwang et al. show how admixing tungsten carbide nanoparticles to the zinc core of a borosilicate-cladded wire leads to intact fibres over lengths significantly exceeding those of metals with high melting points.